2020
DOI: 10.1039/c9nr09572a
|View full text |Cite
|
Sign up to set email alerts
|

An ovarian spheroid based tumor model that represents vascularized tumors and enables the investigation of nanomedicine therapeutics

Abstract: 3D tumors created by simple subcutaneous spheroid injection represents a robust and more vascular murine tumor model and can be a relevant platform to test anti-cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The use of round-bottomed, ULA plates have assisted in the identification of Nectin-4 as essential for adhesion events in early spheroid formation of HGSOC cell lines, and as potential targets to improve chemotherapeutic sensitivity ( Boylan et al, 2020 ). Pre-formed OVCAR-8 spheroids grown in round-bottomed ULA plates and further embedded as single spheroids in Matrigel, developed vascularization after subcutaneous transplantation into athymic nude mice, enabling the evaluation of therapeutics such as the anti-angiogenic bevacizumab and the nano-drug Doxil ® ( Singh et al, 2020 ).…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…The use of round-bottomed, ULA plates have assisted in the identification of Nectin-4 as essential for adhesion events in early spheroid formation of HGSOC cell lines, and as potential targets to improve chemotherapeutic sensitivity ( Boylan et al, 2020 ). Pre-formed OVCAR-8 spheroids grown in round-bottomed ULA plates and further embedded as single spheroids in Matrigel, developed vascularization after subcutaneous transplantation into athymic nude mice, enabling the evaluation of therapeutics such as the anti-angiogenic bevacizumab and the nano-drug Doxil ® ( Singh et al, 2020 ).…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…Since it has been observed in vivo that ovarian cancers often tend to grow in ascites as cell clusters (spheroids) having the potential to metastasize [ 29 , 30 , 31 ], the spheroid model could be particularly relevant to study, in vitro, the ovarian cancer biology and how EVs contribute to cancer progression, taking advantage of an approach that is more consistent with in vivo situation. Indeed, several studies on ovarian cancer have already suggested that the culture model choice can impact, for example, sensitivity to chemotherapeutic agents [ 24 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the most common gynaecological malignant tumour in the clinic, ovarian cancer ranks first in terms of mortality rate among various gynaecological tumours (9). As to its treatment, surgical treatment combined with postoperative adjuvant chemoradiotherapy and biological therapy is the main approach.…”
Section: Discussionmentioning
confidence: 99%